The Home Literacy Environment as a Mediator Between Parental Attitudes Toward Shared Reading and Children’s Linguistic Competencies - Niklas, Frank; Wirth, Astrid; Guffler, Sabrina; Drescher, Nadja; Ehmig, Simone C. (Frontiers in Psychology, 2020)
The home learning environment plays an important role for children’s early competencies development. In particular, the early Home Literacy Environment (HLE) that consists of all literacy resources and interactions in a family that support children’s linguistic and literacy learning, is closely associated with children’s language comprehension and production. A key aspect of the HLE is shared reading that should start early in children’s life and should be part of a regular routine in the family. However, parental attitudes towards (shared) reading have hardly been analyzed. In this longitudinal study, we analyzed the associations between parental attitudes towards shared reading and children’s linguistic competencies and whether this association may be mediated by the HLE. Further, we were interested in change of parental attitudes over time and their association with child and family background characteristics. The sample consisted of N = 133 children with an average age of about 3 years at t1. Children were tested two more times with a six months period in-between each assessment. Parental attitudes towards shared reading, SES, and the HLE were assessed via parental survey. Children’s sentence comprehension, productive language, and grammar were measured with a standardized test battery. Children whose parents had a more positive attitude towards shared reading not only lived in a greater quality HLE, but also performed better in the linguistic tests. In a structural equation model, an indirect effect was found showing that HLE mediated the effect of parental attitudes on children’s linguistic competencies. Further, parental attitudes toward shared reading did not change significantly across t1 to t3 and a lower score in the SES scale was associated with a less positive attitude towards shared reading. Consequently, parental attitudes towards shared reading seem to be an important basis for individual differences in the quality of the HLE and also for children’s linguistic competencies. As these attitudes vary in the context of different family SES backgrounds, they may be a good target for interventions to support the quality of the HLE and young children’s linguistic learning.